1967
DOI: 10.2307/2440884
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental Formation of Polyploidy and its Effect in the Genus Musa

Abstract: Polyploidy was induced in two Musa species and their hybrid by means of immersing newly germinated diploid seedlings in 0.5% aq. colchicine solution. Tetraploid M. balbisiana plants were taller and more robust but had slower growth rate, droopier leaves, fewer suckers, and scantier root systems than the diploids. Tetraploidy affected fruit size and shape in M. balbisiana and in M. acuminata. Tetraploidy did not affect bunch size (the number of fruit‐bearing nodes) in M. acuminata banksii but caused great reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1969
1969
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Simmonds (1954 [143] ) classified the Cavendish group of bananas for plant breeding. Chromosomes of Musa are small and difficult to work with (Vakili, 1967 [157] ). The potential advantages of a breeding scheme to overcome the undesirable characters of tetraploids and to incorporate a second diploid male into the recombination process have been reported (Rowe and Richardson, 1975 [130] ; Rowe, 1984 [131] ; Stover and Buddenhagen, 1986 [148] ).…”
Section: Molecular Genetics Of Bananamentioning
confidence: 99%
“…Simmonds (1954 [143] ) classified the Cavendish group of bananas for plant breeding. Chromosomes of Musa are small and difficult to work with (Vakili, 1967 [157] ). The potential advantages of a breeding scheme to overcome the undesirable characters of tetraploids and to incorporate a second diploid male into the recombination process have been reported (Rowe and Richardson, 1975 [130] ; Rowe, 1984 [131] ; Stover and Buddenhagen, 1986 [148] ).…”
Section: Molecular Genetics Of Bananamentioning
confidence: 99%
“…were studied by Simmonds (1948a,b). Vakili (1967) reported that colchicine derived tetraploids from M. balbisiana were taller and more robust but had slower growth rate, more droopy leaves, fewer suckers and scantier root systems than diploids. Diploids tended to have a right lamina half-broader than the left, while the reverse holds true for polyploids.…”
Section: Ploidy Effects In Phenotypic Appearancementioning
confidence: 99%
“…Colchicine treatment, which results in a doubling of the chromosome number (Vakili, 1962(Vakili, , 1967 has been extensively used on diploid seedlings. For this purpose parental lines were selected to maximize both heterozygosity and the combination of appropriate resistances, quality factors and agronomic characters.…”
Section: The French Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, flow cytometry was introduced, to establish DNA amounts in numerous plants and, hence, determine their ploidy levels. For example, the technique has been used to determine ploidy levels in new Musa clones resulting from treatment with polyploidizing agents such as colchicine (Vakili 1967), from culture tissue (Van Duren et al 1996), and from crossing between different species (Dolezel et al 1997). Moreover, flow cytometry has often been used in studies of the systematics and evolution of different species within a genus (Maxted et al 1991;Godelle et al 1993;Martel et al 1997;Le Thierry d'Ennequin et al 1998).…”
Section: Introductionmentioning
confidence: 99%